Letter from John V. Tunney to Jane Tolmach - John V. Tunney:::::: (1970)
A letter from John V. Tunney, a member of Congress, to Jane Tolmach congratulating her on her election onto the Oxnard City Council and requests her help in his campaign for Senate.